2021
DOI: 10.1080/21655979.2021.1980645
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Tripartite motif-containing 22 (TRIM22)relieved the apoptosis of lens epithelial cells by suppressing the expression of TNF receptor-associated factor 6 (TRAF6)

Abstract: Cataract is a disease that causes severe visual impairment in patients. Recent studies have found that lens epithelial cell apoptosis caused by oxidative damage is the critical cause of cataract. Moreover, TRIM22 could alleviate the ubiquitination of TRAF6. The expression of TRAF6 could activate the p38/MAPK pathway and aggravate the oxidative stress induced damage of lens epithelial cells. However, whether the TRIM22 could alleviate the oxidative stress induced damage of lens epithelial cells by regulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Recently, two further in vitro studies reported an amelioration of oxidative stress-related damage by MAPK suppression through regulation of the NLRP3 inflammasome [206] or through as of yet unelucidated functions of the flavonoid Diosmetin from chrysanthemum, that is used in traditional Chinese medicine [207]. Another recent study has similarly reported corroborating results, with p38 and ERK phosphorylation downregulation also being associated with decreased apoptosis via another proxy (TRIM22) [208]. In a single study reporting an apparently opposite effect, Calmodulin like 3 (CALML3) silencing led to increased apoptosis accompanied by a decreased activation of ERK1/2 and JNK [209].…”
Section: Mapk In Other Ocular Pathophysiologiesmentioning
confidence: 76%
“…Recently, two further in vitro studies reported an amelioration of oxidative stress-related damage by MAPK suppression through regulation of the NLRP3 inflammasome [206] or through as of yet unelucidated functions of the flavonoid Diosmetin from chrysanthemum, that is used in traditional Chinese medicine [207]. Another recent study has similarly reported corroborating results, with p38 and ERK phosphorylation downregulation also being associated with decreased apoptosis via another proxy (TRIM22) [208]. In a single study reporting an apparently opposite effect, Calmodulin like 3 (CALML3) silencing led to increased apoptosis accompanied by a decreased activation of ERK1/2 and JNK [209].…”
Section: Mapk In Other Ocular Pathophysiologiesmentioning
confidence: 76%
“…The overexpression of TRIM22 has been shown to interfere with the clonogenic growth of monocytic cells, [21] while its knockdown attenuated apoptosis in human lens epithelial and cortical neuron cells. [22,23] TRIM22 is assumed to mediate apoptosis such a caspase-dependent pathway, [21,22] NOD2/NF-kB and p53 (gene symbol: TP53) pathway. [24,25] Therefore, it prevents cell proliferation.…”
mentioning
confidence: 99%